Analysis of the Driving Stability of a Multi-Model Driven Electric-Tracked Intelligent Detection Device - Yitian Wang; Huazhen Liu; Linsen Song; Longkai Liang; Yiwen Zhang; Zhenglei Yu; Chunbai Liu; Yanzhong Hao; Meichao Xu; Xinming Zhang; Siying Li (Actuators)
The electric-tracked intelligent detection device is extensively used in engineering exploration and construction. However, in unstructured and complex terrains, its stability is challenged by a high center of gravity and poor road conditions, making the enhancement of its stability analysis crucial. This study is based on tracked vehicle models, constructing kinematic and dynamic equations for the device, and developing virtual and physical prototypes. Combining theoretical analysis, virtual simulations, and physical testing, the study analyzes motion parameters under typical conditions through numerical calculations and simulations. It examines the device’s dynamic characteristics during rapid turns in unstructured terrains. The research identifies variations in motion parameters, determines dynamic stability thresholds, and refines stability analysis methods applicable to the device, establishing evaluation criteria with multiple parameters and weight vectors. In conclusion, the developed models and prototypes help us understand the electric-tracked intelligent detection device’s dynamic characteristics and instability thresholds, enhancing its stability and operational efficiency and providing a theoretical foundation for related engineering machinery development.